Ekonomi Tradisional dan Perubahan Sosial - Humaidi, Humaidi (Institut Agama Islam YPBWI Surabaya, 2024)
This in-depth analysis looks at the complex relationship between traditional economics and social revolution, two interrelated phenomena. The magazine uses a comprehensive, multidisciplinary approach to investigate the relationship between traditional economic processes and societal transformation. This study reveals patterns of change caused by the interaction of social and economic factors by providing a comprehensive analysis of the social structures and cultural values ??that underpin traditional economies. The studies published in this publication provide a comprehensive examination of the difficulties in adapting traditional economies to rapid social change and their implications for the long-term survival and continuity of traditional culture.